Innovative Salt-Free Reactive Dyeing of Cotton Using Cationization with Vicia Faba Bean Pod Waste - Worku Tegegne Molla; Zerihun Kebede; Mintesnot Tesfaye (Sustainable Chemical Engineering, 2025)
This study explores the cationization of cotton fabric using an extract from faba bean husk waste to enable salt-free reactive dyeing. By leveraging natural compounds in the husk, the process enhances dye uptake and fixation, eliminating the need for conventional salt additives. Optimized extraction conditions (including 7.5% HCl, 24-hour treatment, and a 1: 20 material-to-liquor ratio) achieved a 90% dye exhaustion rate and a fixation rate of 51.74%. The cationized fabric exhibited superior color strength (K/S value: 1.5291) compared to conventionally dyed fabric (with a value of 1.3043). Colorfastness to washing, rubbing, and light was comparable to traditional methods, with minimal changes in mechanical properties. This approach demonstrates the potential of faba bean husk as a sustainable cationizing agent, promoting eco-friendly textile dyeing while utilizing agricultural byproducts. The study contributes to reducing environmental hazards and advancing salt-free dyeing technologies.